Belonging to the library: humanising the space for social work education. Issue 8 (16th November 2016) - Sen, Robin; McClelland, Nora; Jowett, Beverley
Abstract: This article describes the running of four Living Libraries on a UK postgraduate social work course. A Living Library is a metaphoric remodelling of a conventional library where people, as authors of their experiences, provide specialist knowledge based on authorial areas of expertise. In the Living Libraries discussed here, 'Living Books' carried stories of social work—their narratives were of lived experiences as people using social care services; as carers in personal relationships with others who use social care services; or, as social work practitioners. The focus of this article is on those Living Libraries involving the participation of the first two of these groups. Drawing on social psychology, phenomenology and human geography, we propose that a Living Library can act as a connective space within social work education by engendering a discursive forum where all participants—people with experiences of services, students, practitioners and social work educators—are given both the freedom and obligation to talk openly about their differential experiences, fears and hopes for social work. Through this process, opportunities are created to consider how improvements that meet all stakeholders' interests may be achieved.